Exploring the Anti-Osteoporotic Effects of n-Hexane Fraction from Cotoneaster wilsonii Nakai: Activation of Runx2 and Osteoblast Differentiation In Vivo - Soyeon Hong; Hee Ju Lee; Da Seul Jung; Saruul Erdenebileg; Hoseong Hwang; Hak Cheol Kwon; Jaeyoung Kwon; Gyhye Yoo (Pharmaceuticals)
Background: Osteoporosis is characterized by the microstructural depletion of bone tissue and decreased bone density, leading to an increased risk of fractures. Cotoneaster wilsonii Nakai, an endemic species of the Korean Peninsula, grows wild in Ulleungdo. In this study, we aimed to investigate the effects of C. wilsonii and its components on osteoporosis. Methods and Results: The alkaline phosphatase (ALP) activity of C. wilsonii extracts and fractions was evaluated in MC3T3-E1 pre-osteoblasts, and the n-hexane fraction (CWH) showed the best properties for ALP activity. The effects of the CWH on bone formation were assessed in MC3T3-E1 cells and ovariectomized mice. Biochemical assays and histological analyses focused on the signaling activation of osteoblast differentiation and osteogenic markers, such as ALP, collagen, and osterix. The CWH significantly activated TGF-β and Wnt signaling, enhancing osteoblast differentiation and bone matrix formation. Notably, CWH treatment improved micro-CT indices, such as femoral bone density, and restored serum osteocalcin levels compared to OVX controls. Conclusions: These results highlight the potential of the C. wilsonii Nakai n-hexane fraction as a promising therapeutic agent for managing osteoporosis.